The Role of Waqf in Strengthening Primary Healthcare Services in Gombe State Rural Communities - Muhammad, Adamu Abubakar; Yakub, Abubakar Aliyu; Mikail, Usman Jibril; Ahmad, Muhammad Hamma-Adama (Asosiasi Profesi Multimedia Indonesia, 2025)
This activity examines the practical role of Waqf (Islamic endowment) in improving primary healthcare services within rural communities of Gombe State, Nigeria. Although primary healthcare is still essential for long-term community well-being, rural areas in Gombe State continue to face obstacles such as inadequate medical personnel, limited infrastructure, and a lack of affordable medications. Utilizing a qualitative case study methodology, data was gathered through interviews with healthcare professionals, Waqf administrators, community leaders, and beneficiaries in three selected rural communities. The study also analyzed existing Waqf-based health projects and explored the administrative systems and legal frameworks of Waqf in Gombe State. The results show that Waqf, when properly institutionalized, has a revolutionary effect on community health education, drug subsidization, the construction of community clinics, and the provision of free maternity and child health services. Waqf's efficacy in the healthcare industry is, however, constrained by the research's discovery of awareness, regulatory enforcement, and stakeholder coordination deficiencies. The report suggests policy frameworks that incorporate Waqf into Gombe State's main healthcare development plan, the establishment of a state-recognized Waqf commission with a focus on healthcare, and the strengthening of local Waqf administrators' capacity. The study concludes that Waqf is a workable Islamic social finance instrument that can relieve the strain on public health resources, empower marginalized rural communities, and help the state achieve universal health care.